2021
DOI: 10.7759/cureus.17997
|View full text |Cite
|
Sign up to set email alerts
|

Giant Meckel’s Diverticulitis Perforation Due to Necrosis

Abstract: Although Meckel's diverticulum (MD) is the most common congenital anomaly of the gastrointestinal tract, its prevalence is approximately 2% in the general population. Most diverticula remain asymptomatic and can be diagnosed with obstruction, perforation, inflammation, and gastrointestinal hemorrhage. The treatment of complicated MD is surgery, but there is no clear treatment recommendation yet for incidentally detected cases. As in the case we present here, the development of perforation due to Giant Meckel's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…When the MD is long with a narrow base, torsion and diverticulitis are commonly associated complications akin to our patient [19] , [20] , [21] , [22] . Intussusception, necrosis, small bowel obstruction and perforation of the ileum are all reported with Giant MDs [10] , [19] , [23] , [24] , [25] , [26] , [27] . Despite the abundance of reported cases, the prevalence of Giant MD is not yet known albeit the majority if not all, being symptomatic on presentation [27] .…”
Section: Discussionmentioning
confidence: 99%
“…When the MD is long with a narrow base, torsion and diverticulitis are commonly associated complications akin to our patient [19] , [20] , [21] , [22] . Intussusception, necrosis, small bowel obstruction and perforation of the ileum are all reported with Giant MDs [10] , [19] , [23] , [24] , [25] , [26] , [27] . Despite the abundance of reported cases, the prevalence of Giant MD is not yet known albeit the majority if not all, being symptomatic on presentation [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, gastrointestinal malformations correspond to approximately 6% of all congenital malformations [6]. MD features are generally quoted by the "rule of 2s" by some authors: is the most common congenital gastrointestinal anomaly, generally found in approximately 2% of the population, twice more likely in males, often found in children at the age of 2 or less, usually located within 2 feet (approximately 60cm) from the ileocecal valve at the antimesenteric border of the ileum (rarely on the mesenteric side), 2 inches (approximately 5 cm) long and may contain 2 types of ectopic mucosas (gastric, mainly, and pancreatic) [8,9]. However, despite the general facts previously presented, based on a recent systematic review, MD is on average 52 cm from the ileocecal valve, 3.05 cm in length and 1.58 cm in diameter [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although Meckel´s statements claim a 25% complication rate, other authors have concluded that such rate is overestimated [10]. In general, Zani et al stated a 4.2% rate of lifetime risk of complications due to MD, while Cullen et al reported the lifetime risk at 6.4% [8,11,12]. Nevertheless, based on a study including 202 patients, the incidence of complications decreases with age and the pediatric population is at the higher risk: 4% risk in patients younger than 20, 2% risk in patients younger than 40 and 0% risk in the elderly [7,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations